Applying conservative power theory for analyzing three-phase X-ray machine impact on distribution systems - Moreira, Alexandre C.; Paredes, Helmo K.M. [UNESP]; Da Silva, Luiz C.P. (Elsevier, 2015)
This article proposes the use of the conservative power theory as an alternative tool to analyze and determine the possible impacts of noisy loads on electrical distribution systems. The orthogonal decomposition of current (or power) of the conservative power theory allows the definition of different performance factors, each factor represents a specific feature of the load (current lag behind the voltage, unbalance and harmonic distortion). Each factor is used to identify potential effects of the X-ray machine on the system. Furthermore, a computational model developed in PSCAD/EMTDC of the three-phase X-ray machine is presented. The analysis and discussions are based on simulations and actual measurements obtained on the terminals of an X-ray machine. The presented results helps to demonstrate the main advantage of the CPT compared to conventional approaches, which is related to its general application for single phase and poly-phase circuits, for asymmetrical and distorted supply voltages, for nonlinear and unbalanced loads and, for variable line frequency.
Keywords: Conservative power theory; Non-linear loads; Power quality; X-ray